Analisis Pengaruh Makro Influencer Dan Mikro Influencer Dalam Kol (Key Opinion Leader) Marketing Terhadap Brand Awareness Skintific - Audrey Jessie Widyadhana (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
Brand awareness is a crucial factor in marketing strategies that influences brand recognition and perception among consumers. This study aims to analyze the impact of macro influencer, Abel Cantika, and micro influencer, Skin Oppa, in Key Opinion Leader (KOL) marketing strategies on brand awareness for the brand Skintific. The research adopts a quantitative approach, employing survey methods and collecting data through questionnaires distributed to social media users. The collected data is analyzed using regression analysis to examine the influence of independent variables (macro influencer and micro influencer) on the dependent variable (brand awareness). The findings indicate that both the macro influencer, Abel Cantika, and the micro influencer, Skin Oppa, significantly influence brand awareness for the Skintific brand. These findings have important implications for marketing practitioners in planning KOL marketing strategies involving both types of influencers to enhance brand awareness and brand image in the beauty industry. The participation of Abel Cantika as a macro influencer demonstrates higher brand recognition and positive perceptions among consumers. On the other hand, Skin Oppa's presence as a micro influencer influences brand awareness through direct interaction and personal recommendations with his engaged followers. These results highlight the importance of combining the impact of macro and micro influencers to create a holistic and effective approach in reaching a wider target audience and strengthening the brand-consumer relationship. Additionally, this study provides deeper insights into the power of KOL influence in shaping brand awareness, which can assist companies in making better strategic decisions to establish their brand presence in a competitive market. The findings underscore the significance of incorporating both macro and micro influencers in KOL marketing strategies, enabling marketers to maximize brand exposure and effectively engage with consumers. Practitioners can leverage the insights from this research to plan and implement impactful KOL marketing campaigns that enhance brand awareness and foster a positive brand image in the beauty industry.